Prospects for additive manufacturing in contact lens devices - Alam,F; Elsherif,M; AlQattan,B; Ali,M; Ahmed,IMG; Salih,A; Antonysamy,DS; Yetisen,AK; Park,S; Butt,H (Advanced Engineering Materials, 2020)
Additive manufacturing (3D printing) has the ability to architect structures at microscale, giving rise to the development of functional contact lenses (CLs) with inbuilt sensing capabilities. 3D printing technology enables fabrication of CLs without surface geometry restrictions. Spherical, nonspherical, symmetric, and asymmetric lenses can be manufactured in an integrated production process. Advantages of 3D printing over conventional techniques include fast and easy production, one-step manufacturing, and no post processing such as grinding or polishing. In addition, and most significantly, 3D printing can create chambers within the wall of the lenses by taking the advantage of computer-aided modeling and layer-by-layer deposition of the materials. These inbuilt chambers can be used for loading drugs and sensing elements. The computer-aided design modeling can allow for manufacturing of patient-specific CLs. This article focuses on the 3D-printing approaches and the challenges faced in fabricating CLs. 3D-printing technology as a technique for manufacturing of CLs is discussed, in addition to the manufacturing challenges and the possible solutions to overcome the obstacles.